IMPROVING ENGLISH VOCABULARY ABILITY THROUGH WORD SEARCH GAME OF THE SEVENTH GRADE STUDENTS OF SMPN 2 ABIANSEMAL IN ACADEMIC YEAR 2009/2010 - Ida Ayu Made Sri Widiastuti (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2011)
The present classroom action study dealt with Improving the Students English Vocabulary Through Word Search Game of the Seventh Grade Students of SMPN 2 Abiansemal in Academic Year 2009/2010. The present classroom action study was basically triggered by the fact that the subjects under study still faced problem in vocabulary mastery. The subjects’ vocabulary problem should be instantaneously solved. Words Search Game were expected to be an effective way in improving and developing the vocabulary mastery of the Sevent Grade Students of SMPN 2 Abiansemal in Academic Year 2009/2010. The present classroom action study made use of pre-test and post-test research design with descriptive and quantitative analysis. It consists of two cycles and in each cycle there are four successive sessions. The present classroom action study was started with administering initial refelction (IR) to the subjects under study which was intended to establish the real preexisting vocabulary mastery of the subjects under study. The comparation of mean score of each session within each cycle shows a significant increase. This grand mean figure convincingly increased much higher than the mean figure of the initial reflection or pretest scores. This grand mean figure convincing reveals that there were significant Improvement of the Students’ English Vocabulary of the Seventh Grade Students of SMPN 2 Abiansemal. The questionnaires which were actually intended to measure the changing learning behavior of the subjects under study in learning vocabulary taught through Words Search Game were administered by the end of the cycle I. The results of the comparative percentage figures obtained for the present class study proved that the subjects' learning behavior changed positively, that was, their attitude and motivation heightened significantly.